A Novel Way of Standardization of ICG Lymphangiography Reporting - Chandrappa, Ashok Basur; Batth, Ritu; Vasudevan, Srikanth; N., Anantheswar Yellambalase; Sreekumar, Dinkar (Indian Journal of Plastic Surgery, 2020)
Background Indocyanine green (ICG) lymphangiography is being increasingly employed to assess the severity of lymphedema, locate the areas of patent linear lymphatics and dermal backflow and plan treatment. This study suggests a novel method of reporting ICG findings in extremities to enable easy understanding among surgeons and physiotherapists and avoid repeat testing when a patient visits a disparate lymphedema center or clinician.Methods A reporting protocol was developed in the lymphedema clinic of the plastic surgery department, and patients were asked to bring along the report in every subsequent review. The ICG findings were recorded on the fluorescence imaging system as well. The report was prepared by one and analyzed by two different clinicians without repeating the test on 10 consecutive patients.Results The interrater reliability of findings in the report was found to be 98.7% among the three clinicians.Conclusion The reporting system was found to be illustratable and reproducible
Keywords: ICG reporting; lymphedema; standardization